A Comparison of Short-Term Peripheral Nerve Stimulation and Pulsed Radiofrequency in the Treatment of Postherpetic Neuralgia - Xu J; Ding Y; Liu B; Wu X; Yang X; Liu Y; Deng H (Journal of Pain Research)
Junfei Xu,* Yongyong Ding,* Bing Liu, Xuehai Wu, Xiaofeng Yang, Yi Liu, Hong Deng Department of Pain, The First People’s Hospital of Zunyi City, Zunyi, Guizhou Province, 563000, People’s Republic of China*These authors contributed equally to this workCorrespondence: Hong Deng, Email dengqiao303@163.comObjective: To compare the application effects of short-term peripheral nerve stimulation (st-PNS) and pulsed radiofrequency (PRF) technology in postherpetic neuralgia (PHN).Methods: A retrospective analysis was conducted on the clinical data of 127 PHN patients from our hospital. Based on the treatment interventions received, patients were divided into a control group (n=63, treated with PRF) and an observation group (n=64, treated with st-PNS). The clinical treatment effects, pain conditions, sleep quality, inflammatory factors [interleukin-6 (IL-6)] levels, quality of life levels, and complication rates were compared between the two groups.Results: The observation group showed significantly higher total treatment effectiveness (93.75%) compared to the control group (80.95%) (P < 0.05). VAS and PSQI scores were significantly improved at 1 week, 1 month, and 3 months post-treatment in both groups (P < 0.05), with the observation group consistently showing better outcomes. Additionally, IL-6 levels decreased significantly, and SF-36 scores improved more in the observation group (P < 0.05). No significant difference was found in complication rates between the two groups (P > 0.05).Conclusion: Compared to PRF treatment, the st-PNS treatment method further improves patients’ pain and sleep quality, reduces inflammatory responses, and enhances quality of life, while also demonstrating better safety.Keywords: short-term peripheral nerve stimulation, pulsed radiofrequency technology, postherpetic neuralgia, application effects, comparative study